PENGGUNAAN INSTAGRAM SEBAGAI MEDIA PROMOSI COMEDY EVENT DI KOTA BENGKULU - Lizaida Jannah; Rasianna BR Saragih; Dionni Ditya Perdana; Delfan Eko Putra (Lafadz Jaya Publisher, 2023)
This study aims to find out the use of Instagram as a distribution strategy for comedy event promotion activities through the Instagram account @standupindo_bkl. This study uses a qualitative method. The informant in this research is the admin of the Instagram account @standupindo_bkl. Data collection techniques in this research used interviews, observation and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The theory used in this research is the AIDDA theory (action, interest, desire, decision, action). The results showed that Stand Up Indo Bengkulu went through three stages to make communicants (followers) experience AIDDA, namely the stage of introducing comedy events to attract attention and interest, the stage of explaining benefits to generate desire, and the stage of convincing followers as communicants to be involved in the comedy event that will be held with the aim of helping followers to decide (decision) and take action (action).